Sitting in : selected writings on jazz, blues, and related topics - Carruth, Hayden, 1921-2008 (University of Iowa Press, 1993)
This collection of essays and poems about the influence of jazz on writing and culture in this country, an expanded edition of the 1986 publication, is a rewarding volume for all those entranced by jazz. Carruth brings his considerable poetic and literary sensibilities to bear on a topic very near to his heart: "Those who are devoted primarily to jazz, to poetry, to all the arts, are also those who contribute more intelligently than others to our practical and moral, political and social, advancement."